Use of Prescription Antiobesity Drugs in the United States. Issue 12 (9th September 2013) - Hampp, Christian; Kang, Elizabeth M.; Borders‐Hemphill, Vicky
<x xml:space="preserve">Abstract</x> Study Objective To examine national trends in prescription antiobesity drug use in the United States. Design Data analysis. Data Source The IMS Health Vector One National and Total Patient Tracker and Encuity Research Treatment Answers databases, the Source Healthcare Analytics Source Lx database, and IMS LifeLink database. Measurements and Main Results National drug use estimates from 1991–2011 were extracted from the IMS Health Vector One National database, and patient characteristics from 2008–2011 were extracted from the Vector One Total Patient Tracker and Encuity Research Treatment Answers databases. The Source Healthcare Analytics Source Lx database was used to examine duration of antiobesity drug use from 2002–2011, with a sensitivity analysis performed using the IMS LifeLink database. In 2011, approximately 2.74 million patients used antiobesity drugs, predominantly phentermine (2.43 million patients). The use of prescription orlistat and sibutramine was relatively uncommon. Eighty‐five percent of antiobesity drug users were female, 62% were aged 17–44 years, and 4.5% had a body mass index of ≤ 24.9 kg/m2. Duration of use was generally short and most patients only had one episode of antiobesity drug use during the observation period. The longest episode of use was 30 days or less in 47–58% of patients. Approximately one quarter of the patients used antiobesity drugs for longer than 90 days, including phentermine and other amphetamine congeners whose labels recommend short‐term use, not exceeding "a few weeks." Only 1.3–4.2% of antiobesity drug users used them for longer than 1 year. Concomitant use of two or more prescription weight‐loss drugs was generally uncommon, although phentermine was dispensed during 13–16% of benzphetamine, diethylpropion, or phendimetrazine episodes of use. Conclusion Phentermine dominated the prescription weight‐loss market. Despite the indication of short‐term use for amphetamine congeners, duration of use was similar to other antiobesity drugs. Nevertheless, the reasons for and implications of the limited duration of use observed with all prescription antiobesity drugs deserve further investigation.